Evaluation of intraparticle mass transfer properties by microcolorimetry - Richard, Klaus Feio Soares (2020)
A novel method for the assessment of intraparticle mass transfer coefficients in porous adsorbents has been developed and tested. The use of microcalorimetry for the estimation of diffusion coefficients is a compelling concept because the technique – already widely used to measure equilibrium properties – might be also used as an alternative to evaluate kinetic properties in a single experiment. A Tian-Calvet microcalorimeter coupled with a manometric/volumetric setup has been used for the experiments. A non-isothermal adsorption model has been derived for the system, with the mass transfer phenomenon being modelled according to different approaches: one is the Linear Driving Force (LDF) model, proposed by Glueckauf (1955); and the other is the intraparticle diffusional control model, developed to estimate the diffusional time constant, Dc/R2. The proposed model has been analyzed and tested for its parametric sensibility, allowing the determination of the measurement limits. Experimental data for a wide variety of sorbents were simulated and the corresponding parameters estimated. The presented method has shown a reasonable capability to estimate the mass transfer properties despite some experimental constraints and sensibility limitations for fast-diffusing species.